THE EFFECT OF AVOCADO JUICE ADMINISTRATION ON LOWERING BLOOD PRESSURE IN PREGNANT WOMEN WITH GESTATIONAL HYPERTENSION IN JULIANA DALIMUNTHE CLINIC KEC. PERCUT SEI TUAN - Krisna, Putri; Syahputri, Deswizar; Lubis, Anita Damayanti (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
Pregnancy is the intrauterine growth and development of the fetus from conception to the beginning of labor and the duration of pregnancy from ovulation to parturition is around 40 weeks and no more than 43 weeks. Gestational hypertension is hypertension that occurs after 20 weeks of pregnancy without urine protein and blood pressure increases >140/90 mmHg. Avocados contain potassium and flavonoids. The potassium in avocado is very high so it can stabilize blood pressure, especially preventing high blood pressure attacks which can be minimized. Meanwhile, flavonoids act as inhibitors of Angiotensin Changing Over Enzyme (ACE), a drug that helps relax veins and arteries to lower blood pressure. The aim of this study was to determine the reduction in blood pressure before and after consuming avocado juice in pregnant women. This type of research is a quasi experiment using a one group pretest-posttest approach. This research uses a purposive sampling technique, where samples are taken according to the criteria set by the researcher. The population in this study was pregnant women with gestational hypertension with a sample of 15 people. The results of bivariate analysis using the Wilcoxon test show that the p-value is 0.000 <0.05, so it can be concluded that there is an effect of giving avocado juice on reducing blood pressure in pregnant women.